Vaccination of guinea pigs using mce operon mutants of Mycobacterium tuberculosis - Obregón Henao, Andrés (2011)
The limited efficacy of the BCG vaccine for tuberculosis, coupled with emerging information suggesting that it is poorly protective against newly emerging strains of Mycobacterium tuberculosis such as the W-Beijing isolates, makes it paramount to search for more potent alternatives. One such class of candidates is attenuated mutants derived from M. tuberculosis itself. We demonstrate here, in an initial short term assay, that mutants derived from disruption of the mce genes of the bacillus were highly protective in guinea pigs exposed by low dose aerosol infection with the virulent W-Beijing isolate SA161. This protection was demonstrated by a significant reduction in the numbers of bacilli harvested from the lungs, and dramatic improvements in lung histopathology.